Dolutegravir: a new HIV integrase inhibitor for the treatment of HIV infection. (November 2014) - Max, Blake; Vibhakar, Sonia
ABSTRACT : Dolutegravir is a second-generation HIV integrase strand transfer inhibitor (INSTI) and the most recent antiretroviral approved for treatment of HIV-1 infection. Dolutegravir in combination with two nucleoside reverse transcriptase inhibitors is one of the preferred regimens recommended by the Department of Health and Human Services HIV treatment guidelines for treatment-naive adults and adolescents. This recommendation is based on clinical trial data where dolutegravir demonstrated superiority compared with guideline preferred regimens containing efavirenz and ritonavir-boosted darunavir and noninferiority compared with first-generation INSTI, raltegravir. Dolutegravir also demonstrated superiority when compared with raltegravir in treatment-experienced, integrase-naive patients and clinical efficacy in patients with resistance to first-generation INSTIs. Overall, dolutegravir has demonstrated excellent tolerability, limited drug interactions, minimal drug resistance and once-daily dosing for treatment-naive patients.